(3JGQjN GdSdWGf Sdje GdYKeGfi eY GdSdWGf bGfUhg GdZhQis - (3CMeO Hf Ydj Hf CMeO Hf RfHd GdQeGd , J HYO (B980 (3g` s ((3eMeO bfGhi GdfSGN s)
(3ChdgG (B:s
( (3ZjQ ehLhO HGdagQS (B) s
(3efbhdg Yf GdfSNI GdeNWhWg HOGQ GdHWQjQcjg GdbHWjI HGdbGgQIs
(3fSNI QGHYI GdLRA GdChd ef fSNI CNQis
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
Keywords: (3GdJGQjNs